Parental Separation and Children's Educational Attainment: A Siblings Approach - Anders Björklund; Marianne Sundström (Institute for the Study of Labor (IZA), 2002)
This article analyzes whether the commonly found negative relationship between parental separation in childhood and educational outcomes is causal or mainly due to selection. We use data on about 100,000 Swedish full biological siblings, born in 1951-64, and perform cross-section and sibling-difference estimations. Outcomes are measured as educational attainment in 1996. Our cross-section analysis show the expected negative and significant relationship, while the relationship is not significant, though precisely estimated, in the siblingdifference analysis. This finding was robust to the sensitivity tests performed and is consistent with selection, rather than causation, being the explanation for the negative relationship.
Keywords: J12; I20; I30; 330; divorce; child welfare; siblings estimators; Bildungsniveau; Kinder; Ehe; Schätzung; Schweden; Scheidung